Answer:
13a² - 39a + 46
Step-by-step explanation:
To find g(a-2)+3g(2a), find each part using the function g(x)=x²-5x+8.
g(a-2) = (a-2)²-5(a-2)+8 = a² - 4a + 4-5a + 10+8 = a² - 9a + 22
3g(2a) = 3{(2a)²-5(2a)+8} = 3{ 4a² - 10a + 8} = 12a² - 30a + 24
Combine the values to find g(a-2)+3g(2a).
g(a-2)+3g(2a) = (a² - 9a + 22) + (12a² - 30a + 24) = 13a² - 39a + 46
-7-5+3=1
-12+3=1
-9≠1. As a result, this is False. Hope it help!
Exact form: 31/35
0.8857142~
Answer:
$28.50
Step-by-step explanation:
It declined $7.50 in 3 days then increased $4 in 2 days
(2,3) , (0,-3) , (-2,1) are the points.
Hope this helps... Let me know if you wanna know anything.